Reconfigurable Microwave Photonic Filter Based on Long Period Gratings Inscribed in Multicore Fibers - Liang Huo; Lin Gan; Li Shen; Ming Tang; Songnian Fu; Weijun Tong (IEEE Photonics Journal)
We propose and experimentally demonstrate a reconfigurable finite impulse response microwave photonic filter (FIR-MPF) based on long period gratings (LPGs) inscribed in multicore fibers. By exploiting two dimensions of optical wavelength and space, intentional inter-core signal switching is realized. For the diversity of optical wavelength, we tune the operation wavelength to change the inter-core power coupling according to the wavelength-dependent characteristic of LPGs. On the other hand, for the diversity of space, we use directional bending of LPGs to achieve switchable spatial channel allocation. Both configurations can implement three different two-tap FIR-MPFs individually. We show a promising solution for reconfigurable radio frequency signal processing in potential with low cost and high efficiency.